Synthesis and Optical Properties of Cu2O and Au-Cu2O core-shell particles - Sai Cong, Doanh; Hai, Pham Nguyen; Bang, Ngac An (VNU Journal of Science: Mathematics - Physics, 2017)
Cuprous oxide (Cu 2 O) and Au-Cu 2 O core-shell nanoparticles were successfully synthesized using the chemical reduction method. The morphology of the synthesized pure Cu 2 Oparticles can be controlled by varying the amount of reducing agent NH 2 OH.HCl. Due to their similar crystal structure and relatively small lattice mismatch Cu 2 O particles are nucleated and locally undergo an epitaxial growth on the surface of the multi-faceted Au seed resulting in a stellated icosahedra Au-Cu 2 O core-shell particle. The extinction spectrum of Cu 2 O particles offew hundred-nm in size is dominated by light scattering, while that of the stellated icosahedra Au-Cu 2 O core-shell particles exhibits the interband absorption of the Cu 2 O shell only. The interband absorption peak undergoes a blue shift as the shell gets thinner. No prominent SPR of the Au nanocore was observed due to a rather thick Cu 2 O shell.